Towards defect-free thin films of the earth-abundant absorber zinc phosphide by nanopatterning. Issue 2 (24th November 2020) - Escobar Steinvall, Simon; Stutz, Elias Z.; Paul, Rajrupa; Zamani, Mahdi; Dzade, Nelson Y.; Piazza, Valerio; Friedl, Martin; de Mestral, Virginie; Leran, Jean-Baptiste; Zamani, Reza R.; Fontcuberta i Morral, Anna
Abstract : Herein, we explore a novel nanopattern-based growth approach to enhance the material quality of the earth-abundant photovoltaic absorber zinc phosphide. Abstract : Large-scale deployment of thin-film photovoltaics will be facilitated through earth-abundant components. Herein, selective area epitaxy and lateral overgrowth epitaxy are explored for the growth of zinc phosphide (Zn3 P2 ), a promising earth-abundant absorber. The ideal growth conditions are elucidated, and the nucleation of single-crystal nanopyramids that subsequently evolve towards coalesced thin-films is demonstrated. The zinc phosphide pyramids exhibit room temperature bandgap luminescence at 1.53 eV, indicating a high-quality material. The electrical properties of zinc phosphide and the junction with the substrate are assessed by conductive atomic force microscopy on n-type, p-type and intrinsic substrates. The measurements are consistent with the p-type characteristic of zinc phosphide. Overall, this constitutes a new, and transferrable, approach for the controlled and tunable growth of high-quality zinc phosphide, a step forward in the quest for earth-abundant photovoltaics.